2015
DOI: 10.20990/aacd.93737
|View full text |Cite
|
Sign up to set email alerts
|

Cam Tavan Algisi İle Örgütsel Vatandaşlik İli̇şki̇si̇: Yükseköğreni̇m Kurumlarinda Görev Yapan Kadin Çalişanlar Üzeri̇nde Bi̇r Araştirma

Abstract: Öz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…İnandı and Tunç (2012), on the other hand, found no strong relationship between women's career obstacles and job satisfaction. Kalkın et al (2015) also found no significant relationship between glass ceiling perception and organizational citizenship behavior.…”
Section: Introductionmentioning
confidence: 71%
“…İnandı and Tunç (2012), on the other hand, found no strong relationship between women's career obstacles and job satisfaction. Kalkın et al (2015) also found no significant relationship between glass ceiling perception and organizational citizenship behavior.…”
Section: Introductionmentioning
confidence: 71%
“…Studies used samples as follows: n=95 (Aksoy, 2018), n=133 (Kalkın, Erdem and Tikici, 2015) (Can, Kaptanoğlu and Halo, 2018). The age of participants is around 26-30 (Can, Kaptanoğlu and Halo, 2018), and 25-30 (Kalkın, Erdem and Tikici, 2015). Table 3 shows the main objectives, findings, and relevancy of each study.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…The part of the scale which consists of 15 questions related to two dimensions called "personal perceptions" and "organizational culture and policies was used in this study. The scale was prepared as a 5-point Likert (1-strongly disagree, 5-strongly agree) scale (Kalkın, Erdem and Tikici, 2015).…”
Section: Which Assessment Tools Were Used To Investigate the Glass Cementioning
confidence: 99%
“…Çalışma yaşamında kadının varlığının her geçen gün arttığı bilinmektedir. Buna karşın aynı artışın yönetici kademelerindeki cinsiyet oranlarına yansımadığı görülmektedir (Kalkın, Erdem, & Tikici, 2015). Kadınların yönetim birimlerinde eşit seviyede temsil edilmeleri için yaklaşık 60 yıl kadar bir süre beklemeleri gerekmektedir (Korkmaz, 2016).…”
Section: Yönetici Dediğin Erkek Olur!unclassified